Pharmacokinetics and tolerability of cinitapride in healthy Chinese volunteers: a randomized, open-label, single- and multiple-dose study. (4th March 2019) - Zhang, Xiong; Wang, Ying; Cheng, Junlin; Hu, Yunfang; Liu, Jianghui; Chen, Jing; Yang, Xingye; Fan, Hongwei
Abstract: Cinitapride (CIN) is a drug for functional dyspepsia. The purpose of the study was to investigate the pharmacokinetics and tolerability of CIN in healthy Chinese volunteers. A randomized, open-label, single- and multiple-dose study was conducted in 12 healthy volunteers. Three different doses of CIN (1, 2, 4 tablets) were given to six groups in the single-dose study, and one tablet (1 mg) of CIN was administered three times a day in the multiple-dose study. Blood samples were collected at predetermined time intervals after CIN dosing and analyzed by LC-MS/MS. Eleven volunteers completed the study. After single dose, the C max and AUC of plasma increased approximately linearly with dosage; no statistically significant differences were found in pharmacokinetic parameters between three dose groups. After multiple doses, there was no significant change in T max and t 1/2 compared with the results from the single dose. After repeated doses, AUC0-t and AUC0-∞ were increased, while CLz/F slightly decreased. And no differences between male and female. The pharmacokinetic parameters of this study were consistent with study results of non-Chinese subjects. Good tolerability was demonstrated in both single- and multiple-dose studies with dosage range from 1 to 4 mg in healthy Chinese subjects.